Premotor cortex is hypoactive during sustained vowel production in individuals with Parkinson’s disease and hypophonia - Manes, Jordan L.; Kurani, Ajay S.; Herschel, Ellen; Roberts, Angela C.; Tjaden, Kris; Parrish, Todd; Corcos, Daniel M. (Frontiers in Human Neuroscience, 2023)
Introduction Hypophonia is a common feature of Parkinson’s disease (PD); however, the contribution of motor cortical activity to reduced phonatory scaling in PD is still not clear. Methods In this study, we employed a sustained vowel production task during functional magnetic resonance imaging to compare brain activity between individuals with PD and hypophonia and an older healthy control (OHC) group. Results When comparing vowel production versus rest, the PD group showed fewer regions with significant BOLD activity compared to OHCs. Within the motor cortices, both OHC and PD groups showed bilateral activation of the laryngeal/phonatory area (LPA) of the primary motor cortex as well as activation of the supplementary motor area. The OHC group also recruited additional activity in the bilateral trunk motor area and right dorsal premotor cortex (PMd). A voxel-wise comparison of PD and HC groups showed that activity in right PMd was significantly lower in the PD group compared to OHC (p < 0.001, uncorrected). Right PMd activity was positively correlated with maximum phonation time in the PD group and negatively correlated with perceptual severity ratings of loudness and pitch. Discussion Our findings suggest that hypoactivation of PMd may be associated with abnormal phonatory control in PD.